Capacity Performance of Dynamic Provisioning in Optical Networks - Ramamurthy, Ravi; Bogdanowicz, Z.; Samieian, S.; Saha, D.; Rajagopalan, B.; Sengupta, Sudipta; Chaudhuri, Surajit; Bala, K. (Invited paper, IEEE/OSA Journal of Lightwave Technology, 2001)
This paper describes an architecture and analyzes the performance of dynamic provisioning of lightpaths in an optical network. In dynamic provisioning, a lightpath is set up in real-time without rearranging the working and protection routes of existing lightpaths, and without the knowledge of future lightpath provisioning events. This paper develops a general model of the physical topology of the optical network, and outlines routing approaches for dynamic provisioning of lightpaths. It analyzes via simulations the performance of dynamically provisioned unprotected, 1+1 protected and mesh-restored lightpaths. The analysis of the efficiency of network utilization of dynamic provisioning focuses on the spare capacity needed for protection, and in particular focuses on the impact of sharing of wavelength channels for mesh-restored lightpaths. The main conclusion from the performance studies is that significant capacity gains are achieved with sharing of wavelength-channels for mesh-restored lightpaths with dynamic provisioning even for sparse topologies, and even at moderate loads.